Cardiomyocyte VEGF Regulates Endothelial Cell GPIHBP1 to Relocate Lipoprotein Lipase to the Coronary Lumen During Diabetes Mellitus. Issue 1 (January 2016) - Chiu, Amy Pei-Ling; Wan, Andrea; Lal, Nathaniel; Zhang, Dahai; Wang, Fulong; Vlodavsky, Israel; Hussein, Bahira; Rodrigues, Brian
Abstract : Objective—: Lipoprotein lipase (LPL)–mediated triglyceride hydrolysis is the major source of fatty acid for cardiac energy. LPL, synthesized in cardiomyocytes, is translocated across endothelial cells (EC) by its transporter glycosylphosphatidylinositol-anchored high-density lipoprotein–binding protein 1 (GPIHBP1). Previously, we have reported an augmentation in coronary LPL, which was linked to an increased expression of GPIHBP1 following moderate diabetes mellitus. We examined the potential mechanism by which hyperglycemia amplifies GPIHBP1. Approach and Results—: Exposure of rat aortic EC to high glucose induced GPIHBP1 expression and amplified LPL shuttling across these cells. This effect coincided with an elevated secretion of heparanase. Incubation of EC with high glucose or latent heparanase resulted in secretion of vascular endothelial growth factor (VEGF). Primary cardiomyocytes, being a rich source of VEGF, when cocultured with EC, restored EC GPIHBP1 that is lost because of cell passaging. Furthermore, recombinant VEGF induced EC GPIHBP1 mRNA and protein expression within 24 hours, an effect that could be prevented by a VEGF neutralizing antibody. This VEGF-induced increase in GPIHBP1 was through Notch signaling that encompassed Delta-like ligand 4 augmentation and nuclear translocation of the Notch intracellular domain. Finally, cardiomyocytes from severely diabetic animals exhibiting attenuation of VEGF were unable to increase EC GPIHBP1 expression and had lower LPL activity at the vascular lumen in perfused hearts. Conclusion—: EC, as the first responders to hyperglycemia, can release heparanase to liberate myocyte VEGF. This growth factor, by activating EC Notch signaling, is responsible for facilitating GPIHBP1-mediated translocation of LPL across EC and regulating LPL-derived fatty acid delivery to the cardiomyocytes. Abstract : Supplemental Digital Content is available in the text.